Launched a collection of outputs on how to design nutrition-sensitive value chain (NSVC) projects - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
In the coming year will be working with IFAD, the World Bank, and others on specific projects and also communications and tools (there will be a web version, for example) and also contributing to development of an FAO e-learning course on NSVCs, based on this work. OICR2221 - https://marlo.cgiar.org/projects/A4NH/study.do?expectedID=2221&edit=true&phaseID=59